Delayed Neuropsychiatric Sequel Following Pediatric Carbon Monoxide Poisoning: A Case Report and Literature Review - Gavrieli, Hila; Noyman, Iris; Hershkovitz, Eli; Taragin, Benjamin; Hazan, Guy (Frontiers in Pediatrics, 2022)
Carbon monoxide (CO) poisoning is a serious health problem. The main pathophysiological mechanism of acute CO poisoning is hypoxia due to the formation of Carboxyhemoglobin (COHb). Delayed neuropsychiatric sequel (DNPS) occur following an interval of several days to several weeks post-CO exposure and can present in many different manifestations ranging from behavioral and mood disorders, to encephalopathy and seizures and cause long term neuropsychiatric sequel. The pathogenesis of DNPS following CO poisoning is not entirely understood and cannot be fully explained by hypoxia-induced encephalopathy. The incidence varies and treatment is unknown. We present a case of a previously healthy 13-year-old boy suffering from DNPS presenting with seizures and encephalopathy and later developing optic nerve damage. Increased awareness to this condition might help diagnose future patients and aid in the understanding of the pathogenesis and treatment options for this poorly understood condition.